2010
DOI: 10.1007/s00253-010-2736-7
|View full text |Cite
|
Sign up to set email alerts
|

High level expression and purification of antimicrobial human cathelicidin LL-37 in Escherichia coli

Abstract: The human antimicrobial peptide LL-37 is a cationic peptide with antimicrobial activity against both Gram-positive and Gram-negative microorganisms. This work describes the development of an expression system based on Escherichia coli capable of high production of the recombinant LL-37. The fusion protein Trx-LL-37 was expressed under control of T7 promoter. The expression of T7 polymerase in the E. coli strain constructed in this work was controlled by regulation mechanisms of the arabinose promoter. The expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 29 publications
0
15
0
2
Order By: Relevance
“…There were many attempts to express cathelicidin in different expression systems using fusion partners such as: thioredoxin, small ubiquitin-related modifier (SUMO), glutathione transferase (GST) and family III cellulose-binding module (CBM) [22,[96][97][98][99][100][101][102]].…”
Section: Expressionmentioning
confidence: 99%
“…There were many attempts to express cathelicidin in different expression systems using fusion partners such as: thioredoxin, small ubiquitin-related modifier (SUMO), glutathione transferase (GST) and family III cellulose-binding module (CBM) [22,[96][97][98][99][100][101][102]].…”
Section: Expressionmentioning
confidence: 99%
“…Its presence was detected in various cells and tissues such as circulating neutrophils, myeloid bone marrow cells, epithelial cells of the skin, and tissues in the gastrointestinal tract, mouth, esophagus, and lungs . Recombinant production of LL‐37 in E. coli and Pichia pastoris have been reported previously . Regarding plant systems, the gene coding for cathelicidin LL‐37 or its variant was integrated into genome of Chinese cabbage ( Brassica rapa var.…”
Section: Introductionmentioning
confidence: 99%
“…One group recently reported that the expression system based on T7 polymerase under the control of lac promoter and thioredoxin as the fusion partners allowed almost six times higher yield than that from our system [Krahulec et al, 2010]. Another recent article reported direct expression of LL-37 in Pichia pastoris, and the band corresponding to LL-37 was barely visible on the gel [Hong et al, 2006], indicating a very low expression.…”
Section: Discussionmentioning
confidence: 75%